2012
DOI: 10.3846/16111699.2011.620145
|View full text |Cite
|
Sign up to set email alerts
|

Ceo Turnover and Corporate Performance Relationship in Pre- And Post- Ifrs Period: Evidence From Turkey

Abstract: This study investigates CEO turnover and corporate performance relationship as a measure of the effectiveness of a corporate governance system. The impact of different financial accounting regimes on the turnover/performance relationship is also analyzed. If systems replace poorly performing managers, they are considered as not ineffective. The results provide evidence that corporate governance systems with poor governance characteristics may not be ineffective, due to the existence of alternative governance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…By 2016, the approximately 140 jurisdictions around the world that required or permitted the use of International Financial Reporting Standards (IFRS) accounted for 60% of the world's gross domestic product (Pacter, 2016). Several studies have analysed this process of converting to IFRS, including the effects of adoption (e.g., Aubert & Grudnitski, 2011;Barbosa Neto, Dias, & Pinheiro, 2009;Bissessur & Hodgson, 2012;Cotter & Wee, 2012;De Souza, Borba, & Zandonai, 2011;Durukan, Ozkan, & Dalkilic, 2012; Guimarães dos Santos, Lima, Freitas, & Lima, 2011;Iatridis, 2012a;Lima, 2011;Martins & Brasil, 2008;Martins & Paulo, 2010;Muller, Oliveira & Lemes, 2011;Riedl, & Sellhorn, 2012;Pelucio-Grecco, Geron, & Formigoni, 2010;Pires & Decourt, 2015;Santos & Calixto, 2010); its relation to earnings management (e.g., Aubert & Grudnitski, 2012;Barth, Landsman, Lang, & Williams, 2012;Fernandes, 2011;Iatridis, 2012b;Jeanjean & Stolowy, 2008;Leventis, Dimitropoulos, & Anandarajan, 2011;Pelucio-Grecco, Geron, Grecco, & Lima, 2014;Shelton, Owens-Jackson, & Robinson, 2011;Tsipouridou & Spathis, 2012;Wang & Campbell, 2012;Zéghal, Chtourou, & Sellami, 2011); and the effects of substituting US Generally Accepted Accounting Principles (GAAP) to prepare financial reports for the US capital market by companies not located in the United States (e.g., Mcenroe & Sullivan, 2011a, 2011bDuh, Hsu, & Alves, 2012;Kim, Li, & Li, 2012). Academics,...…”
Section: Introductionmentioning
confidence: 99%
“…By 2016, the approximately 140 jurisdictions around the world that required or permitted the use of International Financial Reporting Standards (IFRS) accounted for 60% of the world's gross domestic product (Pacter, 2016). Several studies have analysed this process of converting to IFRS, including the effects of adoption (e.g., Aubert & Grudnitski, 2011;Barbosa Neto, Dias, & Pinheiro, 2009;Bissessur & Hodgson, 2012;Cotter & Wee, 2012;De Souza, Borba, & Zandonai, 2011;Durukan, Ozkan, & Dalkilic, 2012; Guimarães dos Santos, Lima, Freitas, & Lima, 2011;Iatridis, 2012a;Lima, 2011;Martins & Brasil, 2008;Martins & Paulo, 2010;Muller, Oliveira & Lemes, 2011;Riedl, & Sellhorn, 2012;Pelucio-Grecco, Geron, & Formigoni, 2010;Pires & Decourt, 2015;Santos & Calixto, 2010); its relation to earnings management (e.g., Aubert & Grudnitski, 2012;Barth, Landsman, Lang, & Williams, 2012;Fernandes, 2011;Iatridis, 2012b;Jeanjean & Stolowy, 2008;Leventis, Dimitropoulos, & Anandarajan, 2011;Pelucio-Grecco, Geron, Grecco, & Lima, 2014;Shelton, Owens-Jackson, & Robinson, 2011;Tsipouridou & Spathis, 2012;Wang & Campbell, 2012;Zéghal, Chtourou, & Sellami, 2011); and the effects of substituting US Generally Accepted Accounting Principles (GAAP) to prepare financial reports for the US capital market by companies not located in the United States (e.g., Mcenroe & Sullivan, 2011a, 2011bDuh, Hsu, & Alves, 2012;Kim, Li, & Li, 2012). Academics,...…”
Section: Introductionmentioning
confidence: 99%
“…Following Barber and Lyon (1996), industry average ROA was measured using median ROA for all listed firms given their industry and size 9 . We used ROA because this measure is less influenced by macroeconomic factors beyond managers' control and is often used in the literature (Durukan et al, 2012; Fiordelisi & Ricci, 2014; He & Fang, 2016; Huson et al, 2001; Lau et al, 2009; Mobbs, 2013; Visintin et al, 2017). We then multiplied our faultline measure by the industry‐adjusted ROA to create our interaction variable 10…”
Section: Methodsmentioning
confidence: 99%
“…Extensive research has indicated that the relationship between corporate performance and CEO dismissal is a measure of the effectiveness of a corporate governance system (Durukan et al, 2012). Empirical studies have shown that firm performance is indeed consistently negatively related to CEO dismissal (Brunello et al, 2003; Denis & Denis, 1995; Fiordelisi & Ricci, 2014; Furtado & Karan, 1990; Kesner & Dalton, 1994; Lau et al, 2009; Ocasio, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Having selected the cases, in reference to earlier studies (Miller, 1993; Romanelli & Tushman, 1994; Rindova, Ferrier & Wiltbank, 2010; Durukan, Ozkan, & Dalkilic, 2012), we used information published in the press about each of the companies to detect strategic changes. As Klarner and Raisch pointed out, these archival data provide ‘consistent information for longitudinal studies, but data from questionnaires and interviews can be contaminated by the “biased recall” of respondents’ (2013: 165).…”
Section: Methodsmentioning
confidence: 99%